Inscrever, repetir e criar: leituras do tempo em Freud - Simões, Alana Araújo Corrêa (2021)
The present work performs a theoretical-conceptual analysis of the different temporal modalities present in Freud's works. For this, a reading that recognizes three temporal movements was systematized. The time of the inscriptions that found and build a psychic apparatus, remodeling a past that becomes current. The time of repetitions, always current and without representation, expressed through the compulsion to repetition, whose functioning is linked to the concept of death drive. The time of creations present in psychic functions of fantasy and mourning, in poetic materials and in the clinic itself, which point to the fiction of a future time. Thus, we present three distinct and inseparable temporalities that move away from the perspective of a clinic that investigates the past as a static plane to present a time of fictionalization of the subject's own time.